Household willingness to accept collection and recycling of waste cooking oil for biodiesel input in Petaling District, Selangor, Malaysia - Kabir, Ibrahim (2014)
In recent years, considerable attention has been given to waste cooking oil (WCO) management. The main reasons for the growing concern for this residue are the externalities associated with its improper discharge on the one hand and viability input in biodiesel production on the other. The programme of WCO collection and recycling for biodiesel input in Petaling district is monitored by the three local authorities under the district; Subang Jaya Municipal Council (MPSJ), Petaling Jaya City Council (MBPJ) and Shah Alam City Council (MBSA). Although, the authorities have been currently struggling to improve the programme, an economic valuation studies could help to gather consumer preferences that can facilitate the programme. This study was conducted to determine the households’ willingness to accept for collection and recycling of WCO for biodiesel input so as to recommend for policies that could encourage consumer participation and propose pricing policy for a quantity of WCO which does not exist currently. Dichotomous Choice Contingent Valuation Method (DC-CVM) was used on samples of 360 households, who were interviewed face to face from February to June, 2013. The questionnaire for this study contain questions basically on households’ socio-demographic background, current practices regarding reuse, disposal and recycling of WCO as well as their perceptions on recycling of WCO into biodiesel. The results of this study have shown that majority of the households positively perceived WCO recycling into biodiesel as significant, yet only a small proportion engaged into it. The logistic regression result revealed that the households are willing to accept for WCO collection and recycling programme and bid amount, income, age, education (university), races (malay and chinese), and gender (female) were the significant determinants of their WTA. The average monthly quantity of WCO generated per household in the district was 2.34 kg, the mean WTA of the households was RM 0.72 per kg of WCO, and the annual environmental protection cost for WCO collection and recycling programme among households in Petaling district was estimated as MYR 9, 438, 829. Findings from this study can be useful to the policy makers, contracted recycling companies and other relevant authorities in their efforts to enhance the effectiveness of WCO collection and recycling programme.